Creating digital collections : a practical guide - Zhang, Allison B.; Gourley, Don. (Oxford : Chandos Pub., 2009)
Libraries recognize the importance of digitizing archival material to improve access to and preservation of their special collections. This book provides a step-by-step guide for creating digital collections, including examples and practical tips. It illustrates concepts with an ongoing case study at the end of each chapter.
Introduction -- Planning and managing digitisation projects -- Selecting material for digitisation -- Metadata strategy -- Digitising material -- Creating metadata -- Designing a user interface for digital collections -- The collection digitisation process and workflow management -- Digital collections management system -- Selecting software and hardware for digital collections management systems -- Documentation -- The knowledge and skills required for creating digital collections -- Conclusion.
Includes bibliographical references (p. 223-229) and index.
uaj 10/05/13
Loans
Keywords: Archival materials -- Digitization; Library materials -- Digitization